Heart and Combined Heart–Kidney Transplantation in Patients With Concomitant Renal Insufficiency and End‐Stage Heart Failure. Issue 2 (26th November 2013) - Schaffer, J. M.; Chiu, P.; Singh, S. K.; Oyer, P. E.; Reitz, B. A.; Mallidi, H. R.
<x xml:space="preserve">Abstract</x> In patients with end‐stage heart failure (ESHF) who are candidates for isolated heart transplant (HRT), dialysis dependence (DD) is considered an indication for combined heart–kidney transplantation (HKT). HKT remains controversial in ESHF transplant candidates with nondialysis‐dependent renal insufficiency (NDDRI). Using United Network for Organ Sharing data, we examined the cumulative incidences of transplant and mortality in patients with DD and NDDRI waitlisted for HKT or HRT. In all groups, 3‐month waitlist mortality was dismal: 31% and 21% for HRT‐ and HKT‐listed patients with DD and 12% and 7% for HRT‐ and HKT‐listed patients with NDDRI. Five‐year posttransplant survival was improved in HKT recipients compared with HRT recipients for both patients with DD (73% vs. 51%, p < 0.001) and NDDRI (80% vs. 69%, p < 0.001). Likewise, multivariable analysis associated HKT with better outcomes than HRT in HKT‐listed patients, although both improved survival. These data argue strongly for HKT in ESHF transplant candidates with DD. However, in patients with NDDRI, HKT must be weighed against the possibility of renal recovery with isolated HRT. Whether HRT (followed by a staged kidney transplant in patients who do not recover renal function after HRT), as opposed to HKT, maximizes organ benefit for patients with NDDRI and ESHF requires assessment. Nevertheless, given their dismal waitlist outcomes and excellent posttransplant results, we suggest that patients with DD and NDDRI with ESHF be considered for early listing and transplant.